Reconocimiento de tipos e individuos geomorfológicos regionales en la costa de Chile - Araya Vergara, José F. (Investigaciones Geográficas: Una mirada desde el sur, 2014)
An approach on the regional coastal geomorphology of Chile is presented here. The used taxonomy is based partly on the H. Valentin,s ideas. A determinate regional unit is defined by her uniform character, configuration and similiar dynamics (genetic aspect), using the notion of common coasts. Each unit integrates regional individuals and regional types, based on coastal key individuals.